VISUAL READING TECHNIQUE INNOVATION IN FILM SCREENING FOR PEOPLE WITH VISUAL DISABILITIES - Kenmada Widjajanto; Ibrahim Adi Surya; Della Dwinanti Sumpena; Soerachman D (JURNAL DARMA AGUNG, 2023)
Naturally, films are created for humans with normal hearing and vision functions. The question is, is it true that people who have visual disabilities are not able to enjoy movies? A Technical Services Unit of Indonesian Ministry of Social Affairs located in Cimahi, West Java, named Sentra Abiyoso, has developed an innovative facilities for people with visual impairments, which is called â€œBioskop Berbisikâ€, meaning whispering cinema. At Bioskop Berbisik, the visually impaired audiences will get help from a visual narrators who tell the storyline of the film. The presence of Bioskop Berbisik Sentra Abiyoso Cimahi is a manifestation of the fifth principle of Pancasila, Social Justice for All Indonesian People, as well as a manifestation of SDGs (Sustainable Development Goals, UN General Assembly Agreement in 2015). As a model of social services for people with visual impairments, the presence of Bioskop Berbisik is interesting and important to observe and study, to see how the beneficiaries feel the sensations, and how the expected management strategy could continue consistently. To get the answer, the writers conducted research using the social experimental method with students of SLBN-A Citeurep Cimahi as respondents.The conclusion of the study provides an answer that Bioskop Berbisik of Sentra Abiyoso Cimahi provides great benefits for people with visual impairments. On the other hand, the management of Sentra Abiyoso as a social service facility under the Ministry of Social Affairs of the Republic of Indonesia needs support from various parties to maintain its sustainability and expand its benefits.